2012
DOI: 10.1242/jeb.073726
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of myoglobins from five whale species with different diving capacities

Abstract: SUMMARYWhales show an exceptionally wide range of diving capabilities and many express high amounts of the O 2 carrier protein myoglobin (Mb) in their muscle tissues, which increases their aerobic diving capacity. Although previous studies have mainly focused on the muscle Mb concentration and O 2 carrying capacity as markers of diving behavior in whales, it still remains unexplored whether whale Mbs differ in their O 2 affinities and nitrite reductase and peroxidase enzymatic activities, all functions that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 44 publications
4
33
2
Order By: Relevance
“…Given the broad range of oxygen affinities that are possible by even single amino acid substitutions, Mb oxygen affinity of vertebrates is conserved within a narrow range to maintain optimal muscle performance. With the exception of the melon-headed whale, the Mb P 50 of the species in this study fell within the range previously reported for birds and mammals (Weber et al, 1974;Nichols and Weber, 1989;Helbo and Fago, 2012).…”
Section: Mb Structural Variants and Oxygen Affinitysupporting
confidence: 88%
See 3 more Smart Citations
“…Given the broad range of oxygen affinities that are possible by even single amino acid substitutions, Mb oxygen affinity of vertebrates is conserved within a narrow range to maintain optimal muscle performance. With the exception of the melon-headed whale, the Mb P 50 of the species in this study fell within the range previously reported for birds and mammals (Weber et al, 1974;Nichols and Weber, 1989;Helbo and Fago, 2012).…”
Section: Mb Structural Variants and Oxygen Affinitysupporting
confidence: 88%
“…Diving species have an array of multilevel adaptations to cope with recurrent breath-holding and the subsequent hypoxia and muscular ischemia (Davis, 2014). Elevated concentrations of respiratory pigments have obvious adaptive advantages for maintaining aerobic metabolism in diving birds and mammals, and recent studies have examined the potential adaptive molecular evolution of the functional properties of these pigments Soegaard et al, 2012;Helbo and Fago, 2012;Schneuer et al, 2012;Mirceta et al, 2013). Oxygen binding globin proteins are obvious candidates for molecular adaptation in diving animals that experience regular hypoxia (Nery et al, 2013a) and Mb has experienced an increased rate of evolution in cetaceans (Nery et al, 2013b).…”
Section: Mb Structural Variants and Oxygen Affinitymentioning
confidence: 99%
See 2 more Smart Citations
“…High Mb content is known to increase oxygen-storage capacity and may also promote intracellular oxygen transport (Wittenberg and Wittenberg, 2006;Koch and Britton, 2008;Mirceta et al, 2013). Diving animals rely heavily on Mb O 2 stores, rather than capillaries, for mitochondrial O 2 supply during dives, and dive duration is positively correlated with Mb concentration (Reed et al, 1994;Butler and Jones, 1997;Kooyman and Ponganis, 1998;Dolar et al, 1999;Helbo and Fago, 2012;Mirceta et al, 2013;Wright and Davis, 2015). Torrent ducks have nearly four times the Mb content reported for nonaquatic birds (Pages and Planas, 1983;Butler and Jones, 1997;Kooyman and Ponganis, 1998;Wright and Davis, 2015), suggesting that they may also have a strong dive capacity.…”
Section: High Mb Content In Torrent Ducksmentioning
confidence: 99%